NASKAH PUBLIKASI PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, KEBIJAKAN DIVIDEN DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2012-2016 - Musripah, 14.05.52.0098; Sunarto, Sunarto (Students Journal of Accounting and Banking, 2018)
This Study aimed to analyze the company size, profitability, divident policy and debt policy to ward the firm value. The population in this study are all companies listed on the Indonesia Stock Exchange in 2012 until 2016. The sample of this study was taken by using purposive sampling technique, so that these were 187 companies got for this study. Data analysis tools used in this research is descriptive analysis and regression analysis berganda. The result of this study showed that the company size has positive and significant effect on firm value, profitability hasnât significant effect on firm value, divident policy hasnât significant effect on firm value, and debt policy hasnât significant effect on firm value. Keywords :Company Size, Profitability, Divident Policy, Debt Policy, Firm Value